The role of pulmonary rehabilitation in severe asthma: a comprehensive review - Guarnieri, Gabriella; Pozza, Michela; Vianello, Andrea (Frontiers in Medicine, 2025)
BackgroundSevere asthma remains a major problem despite pharmacological advances. Pulmonary rehabilitation (PR) is established in chronic respiratory disease but its role in severe asthma is unclear.ObjectivesSummarise evidence on PR in severe and uncontrolled asthma, describe PR-modalities, and outline implementation and research priorities.MethodsNarrative review of systematic reviews and clinical studies of multidimensional PR programmes and isolated components [aerobic training, inspiratory muscle training (IMT), breathing retraining, neuromuscular electrical stimulation (NMES), telerehabilitation]. Outcomes included asthma control, HRQoL, exercise capacity and healthcare utilisation.ResultsMulticomponent PR improves exercise capacity and multiple QoL domains; pooled data show substantial increases in six-minute walk distance. Combined exercise, education and self-management produced clinically meaningful improvements in asthma control and symptoms, notably patients with uncontrolled disease and functional impairment. IMT, NMES and breathing retraining improved inspiratory strength, peripheral muscle function and hyperventilation symptoms. Telerehabilitation expands access but requires attention to digital literacy and adherence. Heterogeneity, small samples and attrition limit generalisability.ConclusionPR is a promising personalised, multidisciplinary adjunct for severe asthma. Larger phenotype-stratified trials, harmonised outcome sets and implementation research are needed to define candidate selection, optimal dose and cost-effectiveness; embedding PR within severe asthma centres may optimise outcomes and reduce healthcare use.